Síntese, caracterização estrutural e análise do potencial catalítico do SrTiO3 e das Perovskitas duplas de Sr1-xKxTiCux/2O3, onde x = 0,2; 0,3 e 0,5, na preparação de biodiesel - Storti, Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work was investigated the synthesis, structural and spectroscopic characterization and the analysis of the catalytic potential of SrTiO3 of perovskita structure and of perovskites doubles Sr1-xKxTiCux/2O3, where x = 0.2, 0.3 and 0.5, in the biodiesel preparation by ethyl route. From the host structure of strontium titanate SrTiO3 were investigated solid solutions containing copper and potassium atoms with the following stoichiometry: Sr0.8K0.2TiCu0.1O3, Sr0.7K0.3TiCu0.15O3 and Sr0.5K0.5TiCu0.25O3, prepared by chemical synthesis using Modified Polyol method. The systems investigated were evaluated using the techniques of thermal analysis (TGA) and differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X-ray diffraction (XRD) and infrared spectroscopy (FTIR). The structural parameters of the investigated systems were determined by the refinement using the Rietveld method, considering the space group Pm m. From the determination of the crystallographic parameter was build the of unit cell of the SrTiO3 using the program Diamond 3.2. The catalytic study was performed from heterogeneous catalysis, with addition of nanoparticles in solution containing vegetable oil and ethyl alcohol. The transesterification process was carried out in a reactor laboratory scale, developed at the LaCCeF, with stirring and controlled temperature. In this process the main products were biodiesel and residual glycerol. During the experiments were controlled the process parameters such as reaction time, catalyst concentration, temperature and stirring degree. In the end of the catalysis reaction was possible to filter and reprocess it to a new reaction, recover the ethanol and calculate the yield of biodiesel from the characterization by gas chromatography coupled to mass spectrometry. The results showed that the Sr0.5K0.5TiCu0.25O3 catalyst is the most efficient for obtention of biodiesel presenting a high conversion in the ...

Neste trabalho foram investigadas a síntese, caracterização estrutural e espectroscópica e a análise do potencial catalítico de catalisadores do tipo perovskita SrTiO3 e das perovskitas duplas de Sr1-xKxTiCux/2O3, onde x = 0,2 , 0,3 e 0,5, na preparação do biodiesel via rota etílica. A partir da estrutura hospedeira do titanato de estrôncio SrTiO3 foram investigadas as soluções sólidas contendo átomos de cobre e potássio com as seguintes estequiometrias: Sr0,8K0,2TiCu0,1O3, Sr0,7K0,3TiCu0,15O3 e Sr0,5K0,5TiCu0,25O3, preparadas por síntese química pelo método Poliol Modificado. Os sistemas investigados foram avaliados utilizando as técnicas de análise térmica (ATG) e calorimetria exploratória diferencial (DSC), microscopia eletrônica de varredura (MEV), difração de raios X (DRX) e espectroscopia vibracional de absorção na região do infravermelho. Os parâmetros estruturais dos sistemas investigados foram determinados pelo refinamento utilizando o método de Rietveld, considerando o grupo espacial Pm m. A partir da determinação dos parâmetros cristalográficos foi construída a célula unitária do SrTiO3 utilizando o programa Diamond 3.2. O estudo catalítico foi realizado a partir da catálise heterogênea, com a adição das nanopartículas em solução contendo óleo vegetal e álcool etílico. O processo de transesterificação foi realizado em um reator de escala laboratorial, desenvolvido junto ao Laboratório de Compósitos e Cerâmicas Funcionais, com sistema de agitação e temperatura controlada. Neste processo, os principais produtos formados foram o biodiesel e o glicerol residual. Ao longo da execução dos experimentos foram controlados os parâmetros do processo, como o tempo da reação, concentração do catalisador, temperatura e o grau de agitação. Ao final da reação foi possível filtrar o catalisador e reprocessá-lo para uma nova reação, recuperar o álcool etílico e calcular o rendimento ...
Keywords: Físico-química; Biodiesel; Catalisadores; Perovskita; Catalise heterogenea; Raios X - Difração; Biodiesel fuels